Reflection on Learning in Teacher Professional Education (PPG) Strategies to Enhance the Competence of Novice Teachers at Universitas Muhammadiyah Sidenreng Rappang - Sam Hermansyah; Buhari; Ibrahim Manda; Andi Sadapotto; Muhammad Hanafi; Andi Asrifan; Syahrir L; Muliani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
Reflection on learning is a vital component of the Teacher Professional Education (PPG) program, particularly in enhancing the competence of novice teachers. At Universitas Muhammadiyah Sidenreng Rappang (UMS Rappang), reflection serves as a mechanism to evaluate and improve teaching practices across pedagogical, professional, social, and personal competencies. This study examines strategies such as daily reflective journals, group discussions, observation and feedback, case studies, and the integration of technology in reflective processes. These strategies aim to develop critical thinking, self-awareness, and innovative teaching approaches among novice teachers. The findings highlight that systematic reflection significantly improves teaching effectiveness, professional development, and student learning outcomes. The structured application of reflective practices empowers novice teachers to become adaptive, professional educators prepared to address the challenges of modern education.